Awards At Work - Susanne Neckermann; Reto Cueni; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2009)
Behavioral economics documents the importance of status and self-image concerns in the workplace, but is largely silent about how to instrumentalize them to induce effort. Awards|widespread in the corporate sector and elsewhere are motivators that derive their value from such social concerns. Panel data from the call center of a large international bank allow us to estimate the impact of receiving an award on e ort. The performance of winners proves to be signi cantly higher than that of comparable nonrecipients after the award has been presented. This increase in work e ort is sizeable, robust, and not driven by reverse causation.
Keywords: C23; J33; M52; 330; Awards; Motivation; Non-monetary Compensation; Event-Study; Incentives